Waste high‐density polyethylene recycling process systems for mitigating plastic pollution through a sustainable design and synthesis paradigm. Issue 4 (2nd January 2021) - Zhao, Xiang; You, Fengqi
Abstract: This article addresses the sustainable design and synthesis of open‐loop recycling process of waste high‐density polyethylene (HDPE) under both environmental and economic criteria. We develop by far the most comprehensive superstructure for producing monomers, aromatic mixtures, and fuels from waste HDPE. The superstructure optimization problem is then formulated as a multi‐objective mixed‐integer nonlinear fractional programming (MINFP) problem to simultaneously optimize the unit net present value (NPV) and unit life cycle environmental impacts. A tailored global optimization algorithm integrating the inexact parametric algorithm with the branch‐and‐refine algorithm is applied to efficiently solve the resulting nonconvex MINFP problem. Results show that the optimal unit NPV ranges from $107.2 to $151.3 per ton of HDPE treated. Moreover, the unit life cycle greenhouse gas emissions of the most environmentally friendly HDPE recycling process are 0.40 ton CO2 ‐eq per ton of HDPE treated, which is 63% of that of the most economically competitive process design.